Keterlibatan Aktif Mahasiswa Dalam Model Flipped Classroom Universitas Negeri Makassar Jurusan Teknik Informatika & Komputer - Nur Qirani Ridhaihi; Tessa Labennu; Asisah Az Zahrah; Andi Shelma Putri Azzahra; Dian Ayu Lestari; Muhammad Ansarullah S Tabbu (Jurnal Pendidikan Terapan, 2023)
The background of this research is the active involvement of students in the flipped classroom model at the Department of Informatics & Computer Engineering, State University of Makassar. The purpose of this study is to determine the active involvement of students in the flipped classroom model. The research method in this study is quantitative. All students of the Department of Informatics & Computer Engineering are the study population. Using the probability sampling technique, a sample of 38 students was obtained. This research was obtained from a collection of online questionnaire filling results filled in by students. Meanwhile, at the data analysis stage, descriptive analysis was carried out. That the activeness of students of the Department of Informatics & Computer Engineering, Makassar State University in the flipped classroom learning model can be said to be good with an average of 2.8775 and a proportion of 2.8775%. The limitation in this study is the number of respondents which is only 38 people which of course is still insufficient to describe the real situation.